Incidencia del Software Educativo en el proceso de enseñanza-aprendizaje de la Matemática - Cajo, Diego Patricio Hidalgo; Coronado, Víctor Manuel Oquendo; Cajo, Byron Geovanny Hidalgo; Cajo, Iván Mesías Hidalgo; Parra, Byron Fernando Castillo; Chanalata, Mercedes Gabriela Montenegro (European Scientific Journal, ESJ, 2018)
The teaching-learning process of Mathematics is complex due to its level of abstraction, making it a challenge for the strategies and didactic resources used by teachers, since the goal is to achieve an adequate academic level in the students, for this it results evident the use of technology since nowadays they play a leading role in society, for that reason the research had as intent the improvement of the learning of the rational numbers of the students of the Educational Unit "Benito Juárez", through the technological resource didactic based on the application of a Mathematical Software. The design of the research is quasi-experimental, correlational-explanatory, the "t" test for independent samples was used to contrast the hypothesis. For data collection, the survey and a test were used that were validated to ensure reliability, the data were analyzed using descriptive statistics. The important results were: (a) better academic performance of the sayers of the experimental group as opposed to the group that did not use it, (b) acceptance and motivation by the didactic resource (c) put into practice their cognitive and motor skills. Therefore, the research provided evidence to use the Mathematical Software as a suitable didactic technological resource for a meaningful learning of Mathematics.